1999
DOI: 10.2174/092986730611220401164817
|View full text |Cite
|
Sign up to set email alerts
|

Design and Applications of Parathyroid Hormone Analogues

Abstract: The endocrine parathyroid hormone (PTH) is the major regulator of serum calcium levels. In contrast, the autocrine/paracrine parathyroid hormone-related peptide (PTHrP) has been associated with organism development. Both are secreted as much larger molecules but have their major functions associated with their N-terminal 34 residues. They share a common receptor expressed in organs critical to PTH function - bone, kidney, and intestine. PTH and PTHrP receptor activation stimulates adenylyl cyclase (AC), phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Our studies here revealed that the same linear hPTH(1−31)NH 2 peptide has the best defined solution structure (Figure ) among all bioactive PTH fragments. It has been shown recently that the anabolic activites of hPTH(1−31)NH 2 can be further enhanced by replacing Lys27 with Leu and by cyclization of the side chains of Glu22 and Lys26 through lactam formation ( , ). The folded structure of hPTH(1−31)NH 2 indeed places the side chains of residues Glu22 and Lys26 in spatial proximity (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our studies here revealed that the same linear hPTH(1−31)NH 2 peptide has the best defined solution structure (Figure ) among all bioactive PTH fragments. It has been shown recently that the anabolic activites of hPTH(1−31)NH 2 can be further enhanced by replacing Lys27 with Leu and by cyclization of the side chains of Glu22 and Lys26 through lactam formation ( , ). The folded structure of hPTH(1−31)NH 2 indeed places the side chains of residues Glu22 and Lys26 in spatial proximity (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it will be extremely important to determine the biological activities of a PTH peptide constrained into the “folded” and V-shape conformation to assess whether the solution structure determined here for hPTH(1−31)NH 2 (Figure ) represents at least one of the bioactive conformations for PTH peptides. This is especially true if one considers the fact that the parathyroid hormone has pleiotropic activities ( ), which may be expressed through the binding to different receptor subtypes of which two have been identified to date (). Better understanding of the structure−activity relationship of the PTH molecules will also come from the characterization of the solution conformations of selectively cyclized PTH analogues and ultimately the three-dimensional structures of PTH peptides in complex with well-defined receptor targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulated data show that the PTH C-terminal helix binds with its hydrophobic face to the long N-terminal extracellular sequence of its receptor and that residues Arg-20, Trp-23, Leu-24, and Leu-28 are critical for the binding (4,48,49). Furthermore, in the context of hPTH(1-31)-NH 2 , the backbone nitrogen of Leu-28, but not Gln-29, is critical.…”
Section: Discussionmentioning
confidence: 99%